CLIMATE JUSTICE, SYMBOLIC REPAIR, AND ETHICAL INTERVENTION THROUGH NARRATIVE AND COMMUNAL HEALING - Francis Kerre (PEOPLE: International Journal of Social Sciences, 2025)
This paper explores how gendered rituals and testimonial practices function as idioms of survival in climate-stressed regions of Kenya—specifically Turkana, Samburu, and Kwale. These regions were selected for their distinct ecological vulnerabilities, ritual traditions, and gendered survival grammars: Turkana’s drought mourning rites, Samburu’s age-set cosmologies, and Kwale’s matrilineal forest rituals offer plural idioms of symbolic repair. Framed by the theme “Climate justice, symbolic repair, and ethical intervention through narrative and communal healing,” the study introduces the concept of idioms of survival to theorize ritual and testimony as embodied archives of climate memory and moral economies of care. Drawing on a braided methodology—participatory narrative ethnography, ritual mapping, and idiomatic prompt design—the paper examines how mourning, fertility, initiation, and ecological testimony encode ethical responses to climate disruption. The study pursues three core objectives: To document and analyze gendered rituals as symbolic technologies of survival To expand testimonial justice into ecological and gendered domains To propose culturally attuned frameworks for climate ethics and adaptation Through case studies and dialogic analysis, the findings reveal how rituals and testimonies offer alternative logics of resilience—ones that challenge technocratic policy and foreground plural cosmologies. The paper contributes to African feminist thought, ritual studies, and climate ethics, while offering practitioner models for ritual-informed programming and policy design. Ultimately, it calls for a reimagining of climate justice—one that listens to the idioms that sustain life.